An Exploratory Spatial–Perceptual Framework for Heritage Revitalization: Mixed-Methods Evidence from Kota Lama Semarang - Bhakti Diliawan, Yudha; Suzanna Ratih Sarı; ., Sukawi (International Journal of Computational and Experimental Science and Engineering, 2026)
Research on urban heritage revitalization faces a critical methodological limitation: the lack of frameworks for statistically testing spatially varying relationships between physical transformation and human perception. This study bridges this gap by developing and validating an integrated Exploratory Spatial–Perceptual Framework (ESPF). The ESPF advances beyond descriptive integration by coupling computational sentiment analysis of geocoded reviews (using a fine-tuned BERT model, F1=0.89) with high-resolution spatial metrics of urban form, and subjecting their relationship to Geographically Weighted Regression (GWR). Applied to Kota Lama Semarang (2003–2024), the ESPF reveals that perceptual outcomes are not uniform but are conditioned by local context. GWR uncovered significant spatial heterogeneity: increased commercial density strongly boosted sentiment in the historic core (β = +0.42), yet eroded environmental perception in peripheral zones (β = -0.38). These divergent associations demonstrate a Contextual Tolerance Threshold, empirically validating a core, yet previously untested, principle of the Historic Urban Landscape (HUL) approach. The study's primary contribution is a replicable, evidence-based framework that transforms HUL from a conceptual model into an operational tool for diagnosing the spatially contingent impacts of heritage policy, offering a critical method for equitable revitalization in Global South cities.